Synthesis of 5-(Trifluoromethyl)-2,3-dihydrofurans through N-Alkylation of Azoles Using Brominated Enones - Pereira, Genilson S.; Mittersteiner, Mateus; Moraes, Paulo A.; Bonacorso, Helio G.; Martins, Marcos A. P.; Zanatta, Nilo (Synthesis, 2025)
We herein present a chemo- and regioselective methodology for the N-alkylation/arylation of azoles (imidazoles, pyrazoles, and triazoles) using 5-bromo-1,1,1-trifluoro-4-alkoxypent-3-en-2-ones (brominated enones) as precursors, in order to selectively obtain N-alkylated azoles containing disubstituted furans or dihydrofurans. The key reaction steps are 1,4-conjugated addition followed by nucleophilic substitution (each promoted by a different nitrogen atom of the azole), which furnish the corresponding 2,5-disubstituted dihydrofurans (24 examples, yields of 37–97%). The limitations of the reaction are explored and it is found that when 2-chlorobenzimidazole is used as a dinucleophile, 5-trifluoromethyl-3-substituted furans are obtained (three examples, yields of 57–67%). The selectivity of the reactions is determined through NMR analysis (including two-dimensional techniques for the 15N nucleus) and single-crystal X-ray analysis.
Keywords: azoles; N-alkylation; N-arylation; dihydrofurans; furans; enones